Properties of particleboard from kenaf (hibiscus cannabinus l.) core and acacia (acacia mangium) wood / Azizul Arifin Abdullah Khir, Jamaludin Kasim and Wan Mohd Nazri Wan Abd Rahman - Abdullah Khir, Azizul Arifin; Kasim, Jamaludin; Wan Abd Rahman, Wan Mohd Nazri (2012)
In this study acacia particles were mixed with kenaf core partricles with ratios of 10, 30 and 50% and produced into particleboard with a resin content of 7% using urea formaldehyde resin. The target board density was 700 kgm-3. From the study it was shown that mixing ratio between acacia and kenaf core particles significantly affected the physical and mechanical properties of particleboard. Boards without any addition of kenaf core showed the highest result for both mechanical and physical properties while boards with 50% addition had the lowest results. All boards made from kenaf core and acacia at all mixing ratios fully satisfied the minimum requirement for the mechanical properties based on European Standards (EN 310). However all boards failed to meet the minimum requirement for the TS value of 12%.